E-book Exposition Text Based Balinese Local Wisdom Increases Elementary School Student Reading Interest - Puryanti, Luh Kade Deni; I Gede Margunayasa (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the limited use of teaching media in learning which causes students to have less than optimal understanding and interest in reading. This has an impact on low student learning outcomes. This study aims to analyze the design, media feasibility, and effectiveness of Balinese local wisdom-based Exposition Text E-Books in Indonesian language subjects to increase the reading interest of grade V elementary school students. The type of research used is quantitative research with a development method using the ADDIE development model. The population and samples in this study were grade V students totaling 20 students. Data collection techniques were carried out by observation, interviews, and questionnaires or questionnaires. This study used quantitative descriptive analysis techniques, qualitative, and inferential statistical analysis (dependent sample t-test). The results of this study are (1) E-Book of Expository Text based on local wisdom in Indonesian language subjects in the form of a website developed with the Canva application. (2) The feasibility of the E-Book is shown from the results of the learning content/material test obtained a percentage of 96.42% (very good), instructional design expert test 91.25% (very good), learning media expert test 92.85% (very good), individual trial 84.09% (very good), and small group trial 89.39% (very good), (3) The effectiveness of the E-Book based on the t-test obtained tcount = 2.222 and ttable = 2.093 which means tcount > ttable, so H0 is rejected and H1 is accepted. Thus, the results of this study indicate that local wisdom-based Expository Text E-Books are feasible and effective to use in Indonesian language subjects to increase the reading interest of grade V elementary school students. Thus, it is expected that the Expository Text E-Book based on Balinese local wisdom has a positive impact in increasing elementary school students' interest in reading.